(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
For more than a year the world has tried to respond to the COVID-19 pandemic. This special issue of the Journal of International Crisis and Risk Communication Research (JICRCR) provides an expert evaluation of how different countries have responded to this global threat. As the pandemic has fundamentally affected most of our lives in a multitude of ways, lessons learned and insights gained from innovative and inclusive research have also advanced theory and practice in public health crisis and risk communication.